The Types of Click Beetles Described by Otto Schwarz from Mexico, Guatemala and Panama (Coleoptera: Elateridae) - Fuller, E.r. (Zootaxa, 2023)
The type specimens of Elateridae described by Otto Schwarz from Mesoamerica are redescribed, reassessed and lectotypes designated. Acanthathous championi (Schwarz), Smiliceroides quadrilineatus (Schwarz), Anoplischiopsis divisus Schwarz, Anoplischius dorsalis Schwarz, Atractosomus nigerrimus Schwarz, and Anchastomorphus minutus Schwarz are retained in their current status. Monocrepidius restinctus Schwarz is reduced to synonymy under Monocrepidius rugicollis Champion. Aeolus mediofasciatus Schwarz is transferred to Monocrepidius Eschscholtz. Tomicephalus bilineatus Schwarz is transferred to Anchastus LeConte, renamed Anchastus lapsus Fuller, and reduced to synonymy under Anchastus seminiger Champion. Crepidius blepharipes Schwarz is restricted to the lectotype and retained in its current status; the other syntypes are unidentified species of Dipropus Germar. Anchastus championi Schwarz is reduced to synonymy under Anchastus tenuistriatus Champion; one syntype is an unidentified species of Dipropus Germar. New country records are documented for A. dorsalis, A. nigerrimus and A. minutus (Guatemala), and A. tenuistriatus (United States).